Liquid crystal thermometry for early detection of hypothermia in newborns in neonatology ward, Sardjito Hospital, Yogyakarta - Tunjung Wibowo; Dwikisworo Setyowireni; A. Samik Wahab (Paediatrica Indonesiana, 2008)
Background Hypothermia in neonates increases the risk ofmortality and morbidity such as infection, coagulation disorders,acidosis and hyaline membrane disease. Mercury thermometer iscommonly used to detect hypothermia in newborns, but it has itis not ecological acceptable, difficult to be sterilized, easily broken,difficult to find in some developing countries and needs sometraining before use. A simple, effective and easily used tool fordetection of hypothermia in newborns is needed.Objective To evaluate the ability of liquid crystal thermometry(LCT) in early detection of newborn hypothermia.Methods This study was conducted in the neonatology ward,Sardjito Hospital. The LCT was placed on the abdominal wall.Digital thermometer measurement and LCT observation wereconducted three times in each patient. LCT’s color and bodytemperature were documented by using a pre-coded questionnaire.Results A total of 268 newborns met the inclusion and exclusioncriteria. The pilot study showed that the inter-observer agreementof LCT was 0.75. Positive likelihood ratio during threemeasurements were 22.9 (95%CI 11.47;45.78), 18.97 (95%CI9.43;38.16) and 22.8 (95%CI 11.34;45.83) respectively.Conclusion LCT exhibits good accuracy and is safe to diagnosehypothermia in newborn.